ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK UMUM YANG DIAWASI LANGSUNG OLEH OTORITAS JASA KEUANGAN PROVINSI SUMATERA BARAT (PERIODE 2015-2022) - Amelia Putri; Fadhila Putri Indriani; Lilis Harianti Hasibuan (MAp (Mathematics and Applications) Journal, 2023)
This study aims to model the factors that influence the profitability of commercial banks which are directly supervised by the Financial Services Authority of West Sumatra Province, namely, Capita Adequacy Ratio (CAR), Operational Income Operational Agency (BOPO), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), and Non Performing Loans (NPL) to Return On Assets (ROA). This study uses secondary data taken based on the time period. The data is taken from the official website of the Financial Services Authority and the Bank Nagari Annual Report. The analysis technique in this study used multiple linear regression using SPSS 16 software. The results of this study indicated that partially CAR, NIM, LDR, and NPL had no significant effect on ROA, while BOPO partially had a significant effect on ROA. The five variables simultaneously have a significant effect on ROA. Furthermore, based on the results of the coefficient of determination test, the value of Adjusted R square 〖(R〗^2) is 75.4%, this means that the ROA can be influenced by the variables CAR, BOPO, NIM, LDR, and NPL, while the remaining 24.6% is explained by other variables not used in research.